THE EFFECT OF USING PUPPET SHOW STRATEGY ON STUDENTS’ READING COMPREHENSION - annesa j. retami; m. syafii s m. syafii s; khairunnas syafii (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
This was aimed at investigating the effect of using Puppet Show strategy on students reading comprehension of narrative texts. The design of this research was quasi experimental design. The population and sample participated was the eighth grade students at Islamic Junior High School Al-Muttaqin Pekanbaru. The number of sampling was selected by using cluster random sampling technique. The technique of analyzing data used was independent sample-T-test and effect size. The result of data analysis showed that there is a significant difference on students’ reading comprehension of narrative texts taught without and by using the Puppet Show Strategy, in which the Sig (2-tailed) 0.000 had less value than 0.05. Thus, Ha is accepted and Ho is rejected. Furthermore, there is a significant effect of using the Puppet Show strategy on the students’ reading comprehension of narrative texts of the eighth grade at Islamic Junior High School Al-Muttaqin Pekanbaru, in which the result of eta squared 0.285 was bigger than 0.21, thus, it was categorized into “modest effect”. This research concluded that teaching reading comprehension by using Puppet Show strategy to the eighth grade students of Islamic Junior High School Al-Muttaqin Pekanbaru was better than students who were taught without using Puppet Show strategy, thus, this research recommended other researchers to conduct the better research by developing the other kinds of puppet as the media in teaching learning processes.